Impact of crop combination and nutrient management on productivity, profitability, and soil health in a coconut-based multistoried cropping system in Kerala, India - V. V. Namitha; Sheeja K. Raj; D. Jacob; P. Shalini Pillai; N. V. Radhakrishnan; Venkatesh Paramesha; Arun Jyoti Nath (Frontiers in Sustainable Food Systems)
Coconut has become the backbone of various agricultural practices in different tracts of Kerala ranging from the sea shores to hilly areas. Kerala was first in area and production earlier but is backward today due to land degradation, industrialization and infrastructure development. This affected the coconut growers and they are facing challenges to cultivate it on a remunerative basis. In this context, there is a need to intensify crop production from the available land area under coconut plantations. Therefore, the current study aims to prove how crop intensification through intercropping in coconut gardens alters system yield and profitability, as well as the soil properties including soil fertility, microbial biomass, and carbon stock. The experiment was conducted at Coconut Research Station, Balaramapuram, Kerala, India, during 2021–2022 in a 60-year-old coconut plantation intercropped with banana, papaya, turmeric, ginger, cassava and elephant foot yam. A randomized complete block design (RCBD) was used to compare the different crop combinations and nutrient rates [100 and 75% Recommended Dose of Fertilizer (RDF)] for the floor crop. Coconut intercropped with banana and turmeric with 75% RDF for turmeric (c1n2) resulted in the highest bunch yield of 138.78 kg unit−1, coconut equivalent yield (NEY) of 475 nuts unit−1 yr−1, and system productivity of 736 nuts unit−1 yr−1. The system also revealed higher economic efficiency, with gross and net returns of $23,852 ha−1 yr−1 and $13,528 ha−1 yr−1 respectively. The soil enzymatic activity, microbial population and soil organic carbon (SOC) were also highest in the system including banana. This study has brought out the fact that proper intercropping and utilization of nutrient resources could improve the yield and the long-term sustainability of coconut farming in Kerala significantly. The results demonstrate that intercropping of coconut with banana and turmeric, along with 100% RDF for coconut and banana and 75% RDF for turmeric, has significantly increased the NEY, system productivity, economic returns, and soil organic carbon (SOC). These findings provide a model for multistoried integration with compatible crops, especially in an aged coconut garden. Further, this study can also be extended for a few more years to analyse the impact on climate and market scenarios.